Integration of sustainability analysis into integrated process design and control framework for distillation columns systems [electronic resource] - Mohamad Zulkhairi Nordin, 1990-, author (2015)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2015